Exploring the role of knowledge management practices in fostering customer relationship management as a catalyst of marketing innovation. Issue 4 (5th October 2015) - Vesna Bosilj Vukšić and Professor Mirjana Pejić Bach, Professor; Garrido-Moreno, Aurora; Lockett, Nigel; Garcia-Morales, Victor
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a research model exploring the link between knowledge management processes and customer relationship management (CRM) performance. It seeks to answer two research questions: What are the effective drivers of knowledge management processes in the context of a CRM initiative? Do these processes make a real impact on CRM performance? Design/methodology/approach – The paper is based on data obtained from a sample of 93 service companies located in Spain. The authors conducted a structural equation modeling analysis using PLS to test the proposed hypotheses. Findings – It was observed that both technological and organizational readiness were effective drivers of knowledge management. However, it was contrasted also that the usage of social media tools was not significantly related to knowledge management. Results show a real impact of knowledge management processes on CRM performance, so companies can understand how to implement successfully those initiatives. Research limitations/implications – The main limitations of the study are that it was based on cross-sectional data and that variables were measured based on the perceptions of general managers. Practical implications – Service companies need to invest in technological infrastructures, and create an appropriate organizational climate (top management support, employees commitment) in order to promote effective knowledge management processes, that will enable CRM success, paving the way for the development of marketing innovations. Originality/value – This is the first empirical work that examines in confirmatory way what are the main drivers of knowledge management processes, including in the analysis the impact of both organizational and technological readiness, and considering also the usage of social media tools, in the context of a CRM initiative.